Dinamika Politik Lokal pada Pemilihan Kepala Desa di Desa Mekarjaya - Arassy, Dewi Fortuna; Fernandes, Reno (Lembaga Yasin AlSys, 2023)
This research is motivated by the existence of deviations that occur within the village administration. According to Sadu Wasistiono 1993 (In Neneng Yani 2016) village head elections cannot be avoided. This study aims to explain the political issues that existed at the time of village head elections in Mekarjaya village. This study uses a qualitative approach. Data collection techniques through observation, interviews and documentation. The results of this study are that the implementation of Pilkades is colored by various political issues. One of the issues in the Pilkades in this village is money politics. The phenomenon of the practice of money politics in Mekarjaya Village carried out by one of these candidates aims to influence people's choices. Even though the money politics that occurred in Mekarjaya Village did not cause conflict, indirectly the practice of money politics in village head elections could undermine the existing democratic system.